Physical and psychological consequences of primary postpartum haemorrhage - Latt, SM (2023)
Background Primary postpartum haemorrhage is characterised by excessive bleeding in the first 24 hours after childbirth. Compared with immediate physical and psychological outcomes, there are relatively fewer studies that have investigated longer-term physical and psychological outcomes of PPH, leading to a significant knowledge gap. The existing literature suggests that cardiovascular disease and mental illness may be longer-term health outcomes of potential importance following PPH.